A simple model of a currency union with endogenous money and saving-investment imbalances - Dirk Ehnts (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2012)
The economic crisis in the euro zone proves that neither the creators of the euro nor today's policy-makers fully understand the functioning of a currency union. Explanations of the macroeconomic relations inside a currency union are therefore in demand. It is now clear that macroeconomic imbalances and debt levels should be part of a model. Traditional textbook models, like the IS-LM-BP or the IS-MR-PC models, respectively, are found lacking on the monetary or the real side or both. The one developed in the following has been created with the purpose of filling this gap and allowing the macroeconomic analysis of a currency union with the help of a simple model featuring endogenous money and saving-investment imbalances.
Keywords: E12; F41; 330; endogenous money; saving-investment imbalances; EMU